Effectiveness of Training Module on Improving Knowledge on Minamata Convention and Best Mercury Hygiene Practices among Dental Professionals in India - Sneha Malhotra; N. Divya Lalitha; Bharathi M. Purohit; Manali Deb Barma; Deepali Agarwal; Upendra Singh Bhadauria; Ajay Logani; Vijay Prakash Mathur; Ritu Duggal; Harsh Priya (Journal of Indian Association of Public Health Dentistry)
Background: Mercury is a highly toxic heavy metal and is one of the top 10 chemicals of major public health concern, according to the World Health Organization. The utilization of mercury in dental amalgam raises concerns about it being an environmental hazard and requires vigilant protocols to be followed during clinical practice. The Minamata Convention (MC) is a global treaty aimed at protecting human health and the environment from the adverse effects of mercury. Studies have been conducted in the past assessing knowledge, attitude, and practice among dentists and patients; however, an interventional strategy using a training module to sensitize dental professionals on mercury hygiene practices and to assess the effectiveness of the training module has not been utilized in the past. Objective: The objective of this study was to assess the knowledge regarding mercury hygiene practices among dental professionals and to evaluate the effectiveness of a training module in improving their knowledge regarding best mercury hygiene practices. Materials and Methods: An interventional study using a training module was conducted with a self-administered pre- and post-questionnaire on 55 dental professionals to assess the knowledge of the participants regarding mercury hygiene practices. Results: A significant (P = 0.01) increase in the mean knowledge scores from 3.89 ± 1.54 to 5.47 ± 1.63 of dental professionals was seen after the training program. About 43% of dental health professionals agreed that dental amalgam is a cause of environmental hazards. Conclusion: The dentists were not well informed about dental amalgam causing environmental hazards. There exists a significant gap in knowledge regarding mercury hygiene and the MC among dental professionals. As India has ratified the MC, there is a need for strong implementation of MC guidelines to prevent contamination of the environment by mercury.